2022
DOI: 10.3399/bjgp.2022.0078
|View full text |Cite
|
Sign up to set email alerts
|

Health and socio-demographic characteristics associated with uptake of seasonal influenza vaccination amongst pregnant women: Retrospective cohort study

Abstract: Pregnant women are at increased risk from influenza, yet maternal influenza vaccination levels remain suboptimal. This study aimed to estimate associations between socio-demographic and health characteristics and seasonal influenza vaccination uptake among pregnant women and understand trends over time to inform interventions to improve vaccine coverage. A retrospective cohort study using linked electronic health records of women in North West London with at least one pregnancy overlapping with an influenza se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 48 publications
1
2
0
Order By: Relevance
“…Interestingly, it can be seen from this study that more pregnant women took the COVID-19 vaccine compared to the flu vaccine (about 30% vs. less than 20%). A similar report was given in a retrospective study [ 28 ], where just under 20% of pregnant women out of about 500,000 got vaccinated against influenza. The fact that influenza is not easily differentiated from other rampant infectious diseases (presenting with fever), such as malaria, which occur in the tropics [ 29 ], may have accounted for less attention being paid to this vaccination.…”
Section: Discussionsupporting
confidence: 70%
“…Interestingly, it can be seen from this study that more pregnant women took the COVID-19 vaccine compared to the flu vaccine (about 30% vs. less than 20%). A similar report was given in a retrospective study [ 28 ], where just under 20% of pregnant women out of about 500,000 got vaccinated against influenza. The fact that influenza is not easily differentiated from other rampant infectious diseases (presenting with fever), such as malaria, which occur in the tropics [ 29 ], may have accounted for less attention being paid to this vaccination.…”
Section: Discussionsupporting
confidence: 70%
“…In the UK, seasonal influenza vaccine uptake in pregnant women has increased in the decade before the COVID-19 pandemic, but still remain low, with rates of 43.6% in 2020/21 taken from Public Health England [ 18 ]. This Irish based prospective cohort study found that the rate of influenza vaccine uptake in pregnancy has risen significantly to 57% (n = 377) from 39% in a similar study in the same hospital in 2016 [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…recently given birth) women and health service providers in South London. We focused on those South London boroughs (Southwark, Lambeth, Lewisham and Croydon) and areas within these boroughs with populations who, based on Index of Multiple Deprivation (IMD) and ethnicity, were less likely to accept or access maternal vaccinations [ 14 – 17 , 24 , 41 ].…”
Section: Methodsmentioning
confidence: 99%